Calculation of Income on Phaco Operations of BPJS Patients at Padang EYE Center Special Hospital in 2018 - Desmiwerita, Desmiwerita (Dinasti International Journal of Economics, Finance & Accounting, 2021)
This study aims to find out how the Pacho Operation Income for BPJS Patients at the Padang Eye Center Special Eye Hospital in 2018. The type of research used is quantitative descriptive research by calculating the amount of income received by the Padang Eye Center Special Eye Hospital for Pacho Operations for BPJS patients based on BPJS rates and based on the rates determined by the Padang Eye Center Special Eye Hospital. From the results of research on the Padang Eye Center Special Eye Hospital, the amount of income based on the tariff set by RSKM PEC was Rp.23,935,000,000 from the number of surgical patients during 2018 as many as 3,395. While the amount of income paid by BPJS is Rp. 23,765,000,000.